Distributed collision control with the integration of packet size for congestion control in wireless sensor networks. Issue 1 (18th July 2014) - Yaakob, Naimah; Khalil, Ibrahim; Atiquzzaman, Mohammed; Habib, Ibrahim; Hu, Jiankun
Abstract: Several great features offered by wireless sensor networks (WSN) result in its wide deployment in various remote and continuous monitoring applications. As such, managing huge collected readings in this domain posted many challenges due to its design limitations. In order to provide seamless data transmission, which is of utmost importance in those delay‐sensitive applications, minimum delay and packet loss occurrence should be considered. Specifically, this paper addresses the common issue of congested networks in WSN with the combination technique of variance‐based distributed contention control (DCC‐V) and packet size optimization. The proposed integration technique, which operates on medium access control layer, takes into consideration the packet size advantages as it plays a key role in determining successful data delivery, given the error‐prone nature of WSN. While ensuring fewer corrupted packets, the proposed contention window (CW) in DCC‐V minimizes the chances of packet collisions and so alleviates congestion. In this technique, CW is determined based on slot utilization and average collision values, which also involve standard deviation measurements. Simulation analysis using network simulator‐2 shows outstanding performance of the proposed solution compared with the existing IEEE 802.15.4 protocol. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper addresses the common issue of congestion in wireless sensor network (WSN) by integrating variance‐based distributed contention control and packet size optimization technique. The consideration of packet size is solely based on its capability in determining successful data delivery, in error‐prone nature of WSN. While ensuring fewer corrupted packets, this method minimizes packet collision rate and so alleviates congestion. Simulation analysis using NS‐2 shows outstanding performance of the proposed solution compared with the existing IEEE 802.15.4 protocol.